2018
DOI: 10.1136/bmj.j5745
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of outcome prediction models for aneurysmal subarachnoid haemorrhage: the SAHIT multinational cohort study

Abstract: Objective -To develop and validate a set of practical prediction tools that reliably estimate the outcome of subarachnoid haemorrhage from ruptured intracranial aneurysms (SAH).Design -Cohort study with logistic regression analysis to combine predictors and treatment modality.Setting -Subarachnoid Haemorrhage International Trialists' (SAHIT) data repository, including randomised clinical trials, prospective observational studies, and hospital registries.Participants -Researchers collaborated to pool datasets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
162
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 34 publications
10
162
1
Order By: Relevance
“…Other recently published aSAH prognostic models which were based on large-scale aSAH-cohorts include the SAFIRE scale, FRESH score and different scores based on the SAHIT cohort [26][27][28] . The SAFIRE model predicted poor functional outcome with an AUROC of 0.73 in the validation cohort and was based on aneurysm size, age, Fisher grade and WFNS 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recently published aSAH prognostic models which were based on large-scale aSAH-cohorts include the SAFIRE scale, FRESH score and different scores based on the SAHIT cohort [26][27][28] . The SAFIRE model predicted poor functional outcome with an AUROC of 0.73 in the validation cohort and was based on aneurysm size, age, Fisher grade and WFNS 26 .…”
Section: Discussionmentioning
confidence: 99%
“…External validation was performed for functional outcome measured by Modified Rankin Scale after 3 months and yielded an AUROC of 0.769. With regards to mortality prediction after 2-12 months, the SAHIT models demonstrated AUROC of 0.76-0.78 and included age, hypertension and WFNS as well as in expanded variations also neuroimaging information and treatment modalities 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor functional outcome after SAH can partially be predicted using models that include factors such as age, World Federation of Neurological Surgeons (WFNS) scale at admission, and premorbid history of hypertension [5]. However, these models do not take into account the inflammatory response after SAH, which is considered to play a key role in the pathogenesis of early brain injury and delayed cerebral ischemia after aneurysmal SAH [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1 The strongest predictor of long-term outcome is the World Federation of Neurological Surgeons (WFNS) grade, 2 but it explained only 12% of the variance in outcome as determined by the Glasgow Outcome Scale (GOS) 3 in the largest study of outcome prediction in aSAH. 4 Some studies have suggested that haptoglobin (HP) genotype may also influence outcome, [5][6][7][8][9] but results are conflicting. 10 A recent meta-analysis found that the HP2 allele was associated with a worse short-term but not long-term outcome.…”
mentioning
confidence: 99%